Misbruik Van Omstandigheden Sebagai Dasar Pembatalan Akta Pengikatan Jual Beli - Angelina, Ajeng Julia; Kartika, Adhitya Widya (Pascasarjana Ilmu Hukum, Universitas Widya Gama Malang, 2023)
Indonesia has legal regulations which are the result of a combination with Dutch law, one of which is civil law in Indonesia which is regulated in the Civil Code or the Civil Code. Over time, legal developments have undergone significant changes following the needs of today's society, one of which is the addition of misbruik van omstandigheden or abuse of circumstances as a new form of handicapped will in the Netherlands, on the other hand, the Indonesian Civil Code has not been added to the Civil Code, but in its implementation, many judges have used the doctrine of abuse of circumstances in deciding a case in court. This research will further discuss the terms of abuse of circumstances based on the study of the decision. The research method used in this study uses a qualitative analysis method with literature study and is a type and type of normative juridical research carried out by examining existing legal norms through library research with the aim of further analyzing the requirements of misbruik van omstandigheden. Based on the results of the research, it can be concluded that the decision of the Mataram District Court Number 234/Pdt.G/2020/PN Mtr has fulfilled the conditions for misuse of circumstances.